MARKETING COMMUNICATION STRATEGY CONDUCTED BY KOLTIVARE HYDROPONIC FARM BEKASI, WEST JAVA - Sonia Az Zahra; Hepi Hapsari; Mahra Arari; Pandi Pardian (Faculty of Animal and Agricultural Science, Diponegoro University, 2022)
The Covid-19 pandemic has had an impact on changing people's consumption patterns to become healthier as seen from the increase in sales of vegetables by 1,900% during the PPKM 2021 period. This is an opportunity for vegetable entrepreneurs, such as the Koltivare Hydroponic Farm company. This study aimed to analyze: 1) The use of marketing communication strategies used by Koltivare Hydroponic Farm, 2) The impact of marketing communications on the volume of demand for vegetables. This research used a qualitative design with the analysis technique of the Miles and Huberman models based on triangulation of data collection techniques. The results of this study indicate that the Koltivare Hydroponic Farm company uses six forms of marketing communications: 1)Advertising which is a form of non-personal communication that aims to provide information and persuasion, both goods and services, 2) Direct marketing is communication that focuses more on direct relationships that are very close to the target market, 3) Interactive marketing is marketing that utilizes technological developments, such as internet, 4) Personal selling is a form of direct communication carried out by sellers to prospective buyers, 5) Sales promotion, namely attracting buyers to make purchases, and 6) Public relations is the creation of a positive image in maintaining relations between business companies and the community. Marketing communication activities that had the most impact on increasing sales volume and market expansion are personal selling, namely activities that meet directly with the target market so that consumers can immediately see the quality of the products purchased and interactive marketing through social media because this activity is able to attract buyers.